Monetary Integration and Optimum Currency Area in ASEAN+3: What we need for a new framework? - Moosavi Mohseni, Reza; Azali, M. (International Journal of Economics and Financial Issues, 2014)
In this paper at first we investigate the viability of creating an optimum currency area (OCA) in the East Asia. The results of a ten-variable VAR model show that forming an OCA for all of the countries in the region is costly and difficult to sustain. But at first five countries called Japan, China, Korea, Malaysia, and the Philippine with symmetric supply shocks can create the OCA. The findings also show that both dollar and yen can be suitable anchor for these countries, but with the exception of Indonesia all other countries are better potential clients of dollar. The final point of this study described the proper arrangements that this region should set up to be successful in this transition. Proper regional exchange rate mechanism and establish supra-national organization and the regional legislation framework seems to be the most important things that this region should be focused on them. Keywords: Monetary Integration; Optimum Currency Area; Currency Boards; ASEAN+3 JEL Classifications: F15; F36